Clinical characteristics and thrombotic risk of atrial fibrillation with obstructive sleep apnea: results from a multi-center atrial fibrillation registry study - Xu, Wei; Yang, Yan-min; Zhu, Jun; Wu, Shuang; Wang, Juan; Zhang, Han; Shao, Xing-hui; Mo, Ran; Tan, Jiang-shan; Wang, Jing-yang (BMC cardiovascular disorders, 2022)
Background Sleep apnea is a risk factor for atrial fibrillation (AF) but it is underdiagnosed. Whether obstructive sleep apnea (OSA) is correlated with thrombotic risk in AF remains unclear. The aim of the present study was to analyze the clinical characteristics and assess the thrombotic risk of AF with OSA. Methods In the present registry study,1990 consecutive patients with AF from 20 centers were enrolled. The patients were divided into 2 groups depending on whether they presented with both AF and OSA. All the patients were followed up for 1 year to evaluate the incidences of stroke and non-central nervous system (CNS) embolism. Results Of the 1990 AF patients, 70 (3.5%) and 1920 (96.5%) patients were in the OSA group and non-OSA group, respectively. The results of the multivariate logistic model analysis showed that male sex, body mass index (BMI), smoking, and major bleeding history were independent risk factors for patients with AF and OSA. The comparison of the Kaplan-Meier curves using the log-rank test revealed that AF with OSA was correlated with an increased risk of non-CNS embolism (p < 0.01). After multivariate adjustments were performed, OSA remained an independent risk factor for non-CNS embolism (HR 5.42, 95% CI 1.34-22.01, p = 0.02), but was not correlated with the risk of stroke in patients with AF. Conclusions The present study revealed that male sex, high BMI values, smoking, and major bleeding history were independent risk factors for patients with AF and OSA. Moreover, OSA was an independent risk factor for non-CNS embolism in AF. Our results indicate that non-CNS embolism requires focus in patients with AF and OSA. Keywords: Atrial fibrillation, Non-central nervous system embolism, Sleep apnea, Stroke, Thrombosis